Psychoeducation Mindfulness to Reduce Anxiety in the Elderly in Rame Hamlet, Pilang Village, Wonoayu District, Sidoarjo Regency - Synta Dea Damayanti; Eko Hardi Ansyah (Salus Publica: Journal of Community Service, 2025)
This study aims to determine the effectiveness of mindfulness psychoeducation in increasing understanding of anxiety in the elderly in Rame Hamlet, Pilang Village, Wonoayu District, Sidoarjo Regency. The elderly often face anxiety related to age and health changes, so mindfulness psychoeducation is expected to increase their understanding of how to manage anxiety. A total of 25 elderly people participated in the psychoeducation activities provided in one session, and changes in understanding were measured using pre-test and post-test. Data were analyzed using t-test to compare the scores of understanding before and after psychoeducation. The results showed a significant difference in understanding of anxiety (t = 8.069, p < 0.001), indicating that mindfulness psychoeducation is effective in improving understanding of anxiety in the elderly.